SWAM: A logic-based mobile agent programming language for the Semantic Web - Crasso, Marco Patricio (2011)
Once a big repository of static data, the Web has been gradually evolved into a worldwide network of information and services known as the Semantic Web. This environment allows programs to autonomously interact with Web-accessible information and services. In this sense, mobile agent technology could help in efficiently exploiting this relatively new Web in a fully automated way, since Semantic Web resources are described in a computer-understandable way. In this paper, we present SWAM, a platform for building and deploying Prolog-based intelligent mobile agents on the Semantic Web. The article also reports examples and experimental results in order to illustrate as well as to assess the benefits of SWAM.